2021
DOI: 10.3892/etm.2021.9666
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑598 inhibits the growth of triple negative breast cancer cells by targeting JAG1

Abstract: Triple-negative breast cancer (TNBC) has an aggressive phenotype and a poor outcome. The discovery that dysregulated microRNAs (miRNAs) play an important role in tumor progression has led to the suggestion that miRNAs (miRs) could be a potential target for the treatment of TNBC. In the present study, it was demonstrated that miR-598 expression was significantly decreased in TNBC tissues and was related to the degree of lymph node metastasis of patients with TNBC. Ectopic expression of miR-598 suppressed viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, due to the tumor-speci c and manifold in uence of hypoxia and the divergence of miRNAs and vice versa, the crosstalk between hypoxic signaling and miRNA biogenesis is still relatively unexplored, and the potential therapeutic setting remains to be established. Studies have shown that miR-598 is a tumor suppressor and is downregulated in triple-negative breast cancer [11], retinoblastoma [7], osteosarcoma [12], colorectal cancer [13] and gastric cancer [14]. In addition, miR-598 was shown to suppress the proliferation and metastasis of multiple tumors and was associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the tumor-speci c and manifold in uence of hypoxia and the divergence of miRNAs and vice versa, the crosstalk between hypoxic signaling and miRNA biogenesis is still relatively unexplored, and the potential therapeutic setting remains to be established. Studies have shown that miR-598 is a tumor suppressor and is downregulated in triple-negative breast cancer [11], retinoblastoma [7], osteosarcoma [12], colorectal cancer [13] and gastric cancer [14]. In addition, miR-598 was shown to suppress the proliferation and metastasis of multiple tumors and was associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Moreover, the role of miR598 in the repression of TNBC was triggered via targeting JAG1. 6 It was demonstrated that intravenous injection of miR206 robustly reduced the mass of xenograft tumors of TNBC. 7 In addition, eight weeks after transplantation of TNBC cells transfected with miR355 to nude mice, slower tumor growth compared to the control group was detected.…”
Section: Introductionmentioning
confidence: 99%